Randomized trial of radiofrequency ablation versus conventional surgery for superficial venous insufficiency: if you don’t tell, they won’t know (Clinics, 2016)
OBJECTIVES: This study compared radiofrequency ablation versus conventional surgery in patients who had not undergone previous treatment for bilateral great saphenous vein insufficiency, with each patient serving as his own control. METHOD: This was a randomized controlled trial that included 18 patients and was carried out between November 2013 and May 2015. Each of the lower limbs of each patient was randomly assigned to undergo either radiofrequency ablation or conventional surgery. Clinical features (hyperpigmentation, hematoma, aesthetics, pain, skin burn, nerve injury, and thrombophlebitis) were evaluated at one week, one month, and six months postoperatively. Hemodynamic assessments (presence of resection or occlusion of the great saphenous vein and recurrent reflux in the sapheno-femoral junction and in the great saphenous vein) were performed at one month, six months, and 12 months postoperatively. The independent observer (a physician not involved in the original operation), patient, and duplex ultrasonographer were not made aware of the treatment done in each case. Clinicaltrials.gov: NCT02588911. RESULTS: Among the clinical variables analyzed, only the aesthetic evaluation by the physicians was significant, with radiofrequency ablation being considered better than conventional surgery (average, 0.91 points higher: standard deviation: 0.31; 95% confidence interval: -1.51, -0.30; p=0.003). However, in our study, we observed primary success rates of 80% for radiofrequency ablation and 100% for conventional surgery. CONCLUSIONS: If the physician is not required to inform the patient as to the technique being performed, the patient will not be able to identify the technique based on the signs and symptoms. Our study revealed that both techniques led to high levels of patient satisfaction, but our results favor the choice of conventional surgery over radiofrequency ablation, as patients who underwent conventional surgery had better hemodynamic assessments.